Assessment of Right Ventricular Function With CT and Echocardiography in Patients With Severe Acute Respiratory Distress Syndrome on Extracorporeal Membrane Oxygenation. (22nd February 2021) - Vogel, Dominik J.; Fabbri, Ambra; Falvo, Andrea; Powell-Tuck, Jonah; Desai, Nishita; Vasques, Francesco; Meadows, Chris; Ioannou, Nicholas; Glover, Guy; Brame, Aimée; Sherren, Peter; Retter, Andrew; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Changes in right ventricular size and function are frequently observed in patients with severe acute respiratory distress syndrome. The majority of patients who receive venovenous extracorporeal membrane oxygenation undergo chest CT and transthoracic echocardiography. The aims of this study were to compare the use of CT and transthoracic echocardiography to evaluate the right ventricular function and to determine the prevalence of acute cor pulmonale in this patient population. Design: Observational, retrospective, single-center, cohort study. Setting: Severe respiratory failure and extracorporeal membrane oxygenation center. Patients: About 107 patients with severe acute respiratory distress syndrome managed with venovenous extracorporeal membrane oxygenation. Interventions: Chest CT to evaluate right ventricular size and transthoracic echocardiography to evaluate right ventricular size and function. Measurements and Main Results: All 107 patients had a qualitative assessment of right ventricular size and function on transthoracic echocardiography. Quantitative measurements were available in 54 patients (50%) who underwent transthoracic echocardiography and in 107 of patients (100%) who received CT. Right ventricular dilatation was defined as a right ventricle end-diastolic diameter greater than left ventricular end-diastolic diameter upon visual assessment or an right ventricle end-diastolic diameter/left ventricular end-diastolic diameter and/or right ventricle cavity area/left ventricular cavity area of greater than 0.9. Right ventricle systolic function was visually estimated as being normal or impaired (visual right ventricular systolic impairment). The right ventricle was found to be dilated in 38/107 patients (36%) and in 58/107 patients (54%), using transthoracic echocardiography or CT right ventricle end-diastolic diameter/left ventricular end-diastolic diameter, respectively. When the CT right ventricle cavity/left ventricular cavity area criterion was used, the right ventricle was dilated in 19/107 patients (18%). About 33/107 patients (31%) exhibited visual right ventricular systolic impairment. Transthoracic echocardiography right ventricle end-diastolic diameter/left ventricular end-diastolic diameter showed good agreement with CT right ventricle cavity/left ventricular cavity area ( R 2 = 0.57; p < 0.01). A CT right ventricle cavity/left ventricular cavity area greater than 0.9 provided the optimal cutoff for acute cor pulmonale on transthoracic echocardiography with an AUC of 0.78. Acute cor pulmonale was defined by the presence of a right ventricle "D-shape" and quantitative right ventricle dilatation on transthoracic echocardiography or a right ventricle cavity/left ventricular cavity area greater than 0.9 on CT. A diagnosis of acute cor pulmonale was made in 9/54 (14% patients) on transthoracic echocardiography and in 19/107 (18%) on CT. Conclusions: Changes in right ventricular size and function are common in patients with severe acute respiratory distress syndrome requiring venovenous extracorporeal membrane oxygenation with up to 18% showing imaging evidence of acute cor pulmonale. A CT right ventricular cavity /left ventricular cavity area greater than 0.9 is indicative of impaired right ventricular systolic function.